Giant Cell Angiofibroma in Unusual Localization: A Case Report - Emel Ebru Pala; Rafet Beyhan; Umit Bayol; Suheyla Cumurcu; Ulku Kucuk (Case Reports in Pathology)
Giant cell angiofibroma (GCA) was initially described as a potentially recurrent tumor in the orbit of adults. However, it is now recognized that it can also present in other locations. The morphological hallmark is a richly vascularized patternless spindle cell proliferation containing pseudovascular spaces and floret like multinucleate giant cells. Our case was a 32-years-old female complaining of painless solitary nodule arising on the occipital region of the scalp, which was diagnosed as giant cell angiofibroma. We report the case because of its extremely rare localization.